2001
DOI: 10.1016/s0002-9440(10)64091-6
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Repair After Menstruation Involves Regulation of Vascular Endothelial Growth Factor-Receptor Phosphorylation by sFLT-1

Abstract: Regeneration of the endometrium after menstruation requires a rapid and highly organized vascular response. Potential regulators of this process include members of the vascular endothelial growth factor (VEGF) family of proteins and their receptors. Although VEGF expression has been detected in the endometrium, the relationship between VEGF production, receptor activation, and endothelial cell proliferation during the endometrial cycle is poorly understood. To better ascertain the relevance of VEGF family memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
40
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 60 publications
10
40
1
Order By: Relevance
“…If such vasoconstriction occurred in the endometrium in situ, it would provide a possible mechanism for vessel repair through hypoxia-induced upregulation of VEGFA. Several studies have observed the highest expression of VEGFA during the menstrual phase of the menstrual cycle (CharnockJones et al 1993, Sharkey et al 2000, Graubert et al 2001. In addition, more SLC2A1 (a glucose transporter and marker of anaerobic metabolism that is induced by ischaemia, previously known as GLUT1) was found in endometrial samples from menstruating women in comparison to proliferative or secretory phase samples (Graubert et al 2001).…”
Section: Vascular Endothelial Growth Factor-amentioning
confidence: 98%
See 3 more Smart Citations
“…If such vasoconstriction occurred in the endometrium in situ, it would provide a possible mechanism for vessel repair through hypoxia-induced upregulation of VEGFA. Several studies have observed the highest expression of VEGFA during the menstrual phase of the menstrual cycle (CharnockJones et al 1993, Sharkey et al 2000, Graubert et al 2001. In addition, more SLC2A1 (a glucose transporter and marker of anaerobic metabolism that is induced by ischaemia, previously known as GLUT1) was found in endometrial samples from menstruating women in comparison to proliferative or secretory phase samples (Graubert et al 2001).…”
Section: Vascular Endothelial Growth Factor-amentioning
confidence: 98%
“…VEGFA mRNA and protein are expressed by both the epithelium and stroma of the primate and rodent endometrium, with temporal and spatial changes apparent during the menstrual cycle (Charnock-Jones et al 1993, Shifren et al 1996, Torry et al 1996, Sharkey et al 2000, Graubert et al 2001, Lee et al 2008. The expression patterns reported are not consistent and are therefore difficult to interpret.…”
Section: Vascular Endothelial Growth Factor-amentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro studies have demonstrated that E 2 increased the expression of VEGFA mRNA in a dose-and timedependent manner in cultured human endometrial stromal (Zhang et al 1995, Bausero et al 1998, Huang et al 1998, Graubert et al 2001) and epithelial cells (Zhang et al 1995) and in isolated endometrial endothelial cells (Shifren et al 1996). In vivo research with various animal models has produced more variable results.…”
Section: Introductionmentioning
confidence: 99%